2020
DOI: 10.21203/rs.3.rs-21876/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long-term safety and effectiveness of etanercept in JIA: an 18-year experience from the BIKER registry

Abstract: Background: At present, etanercept represents the most commonly prescribed biologic agent for juvenile idiopathic arthritis (JIA) treatment. Children and adolescents with JIA are often treated with etanercept over long periods, sometimes even into adulthood. The objectives of this analysis were to determine the long-term safety of etanercept compared to a biologic-naïve cohort, and to assess the long-term treatment response upon continuous etanercept exposure using data from the German biologics registry (BiKe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…It would have been interesting to compare the effect of treatment on different JIA categories, but our study cohort was too small for this. Children with JIA treated with ETN have been found to have an increased risk for IBD [16], and since changes in the gut microbiota have been associated with the development of IBD [35], it is important to further examine the possible effect of ETN treatment on gut microbiota in a larger study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It would have been interesting to compare the effect of treatment on different JIA categories, but our study cohort was too small for this. Children with JIA treated with ETN have been found to have an increased risk for IBD [16], and since changes in the gut microbiota have been associated with the development of IBD [35], it is important to further examine the possible effect of ETN treatment on gut microbiota in a larger study.…”
Section: Discussionmentioning
confidence: 99%
“…In a study on mice with proteoglycaninduced arthritis, treatment with ETN restored an increased gut permeability and changed the microbiota composition to one more similar to that in control mice [15]. On the other hand, a large German register study has shown an increased risk for inflammatory bowel disease (IBD) in children with JIA treated with ETN as monotherapy [16]. This increases the indication for studying the impact of ETN treatment on the gut microbiota in children with JIA.…”
Section: Introductionmentioning
confidence: 99%